Survival analysis with interval-censored data : a practical approach with R, SAS and WinBUGS /: a practical approach with R, SAS and WinBUGS. (2017) - Komárek, Arnošt; Bogaerts, Kris; Lesaffre, Emmanuel
No abstract available